Dermoscopic Photographs Impact Confidence and Management of Remotely Triaged Skin Lesions - Rogers, Tova; McCrary, Myles Randolph; Yeung, Howa; Krueger, Loren; Chen, Suephy (Dermatology Practical & Conceptual, 2022)
Background: Improving remote triage is crucial given expansions in teledermatology and with limited in-person care during COVID-19. In addition to clinical pictures, dermoscopic images may provide utility for triage. Objective: To determine if dermoscopic photographs enhance confidence, triage accuracy, and triage prioritization for teledermatology. Methods: In this parallel convergent mixed-methods study, a cohort of dermatologists and residents assessed skin lesions using clinical and dermoscopic photographs. For each case, participants viewed a clinical photograph and determined diagnostic category, management, urgency, and decision-making confidence. They subsequently viewed the associated dermoscopy and answered the same questions. A moderated focus group discussion followed to explore perceptions on the role of dermoscopy in teledermatology. Results: Dermoscopy improved recognition of malignancies by 23% and significantly reduced triage urgency measures for non-malignant lesions. Participants endorsed specific utilities of teledermoscopy, such as for pigmented lesions, with limitations including poor image quality. Conclusions: Dermoscopic photographs may be useful when remotely triaging skin lesions. Standardized imaging protocols are needed.